Transverse colonic volvulus after resection of sigmoid volvulus: Presentation of a case report - Eldirdiri, Samaual (Int J Surg Case Rep, 2019)
INTRODUCTION: Colonic volvulus is the third leading cause of colonic obstruction in the world following colorectal cancer and complicated sigmoid diverticulitis. Transverse colon is the rarest among other colonic volvulus. Moreover synchronous/metachronous transverse colonic volvulus is extremely rare condition with only few case reported in the literature, we hereby report this case of metachronous transverse colonic volvulus years after sigmoidectomy for sigmoid volvulus CASE PRESENTATION: A case of transverse colon volvulus in elderly male with history of chronic constipation and a previous history of a sigmoid volvulus resection few years ago. He presented as an emergency with typical features of acute large bowel obstruction. He was successfully managed with a good out come DISCUSSION: We discuss the presentation, diagnosis and surgical management with a literature review of this case of a metachronous transverse colonic volvulus. CONCLUSION: Metachronous colonic volvulus is an extremely rare cause of large bowel obstruction and should be considered as a differential diagnosis especially in geographic areas with high rate of volvulus or in those with underlying risk factor